2021
DOI: 10.1002/bit.27953
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of protein engineering and glycoengineering to fine‐tune antibody glycosylation and its impact on effector functions

Abstract: The N‐glycan pattern of an IgG antibody, attached at a conserved site within the fragment crystallizable (Fc) region, is a critical antibody quality attribute whose structural variability can also impact antibody function. For tailoring the Fc glycoprofile, glycoengineering in cell lines as well as Fc amino acid mutations have been applied. Multiple glycoengineered Chinese hamster ovary cell lines were generated, including defucosylated (FUT8KO), α‐2,6‐sialylated (ST6KI), and defucosylated α‐2,6‐sialylated (FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The extracted glycans were subjected to Carbocolumn N-glycan clean-up and stored at 4 °C for Matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) analysis. The detailed procedure for Carbocolumn N-glycan clean-up was provided in our previous publication . The de- N -glycosylated protein-bead mixture was subjected to β-elimination to release O-glycans, followed by permethylation, which were described in detail in our previous work .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted glycans were subjected to Carbocolumn N-glycan clean-up and stored at 4 °C for Matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) analysis. The detailed procedure for Carbocolumn N-glycan clean-up was provided in our previous publication . The de- N -glycosylated protein-bead mixture was subjected to β-elimination to release O-glycans, followed by permethylation, which were described in detail in our previous work .…”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure for Carbocolumn Nglycan clean-up was provided in our previous publication. 44 The de-N-glycosylated protein-bead mixture was subjected to β-elimination to release O-glycans, followed by permethylation, which were described in detail in our previous work. 21 The purified glycan was analyzed using a Bruker AutoFlex MALDI-TOF spectrometer in positive reflection ion mode.…”
Section: Glycan Maldi-tof Analysismentioning
confidence: 99%
“…IgG N-glycan biosynthesis starts in the endoplasmic reticulum with the addition of a pyrophosphate-dolichol precursor (Dol-P, Glc3Man9GlcNAc2) to the Asn 297 Nglycosylation site of IgG. This structure is then trimmed by glucosidases and mannosidases, as the process moves to the Golgi, leading to the formation of high mannose, hybrid and the complex types N-glycans (26,(30)(31)(32)(33). The main enzymatic reactions taking place in the Golgi are summarized in Figure 2.…”
Section: The Biosynthesis Of Human Igg N-linked Glycansmentioning
confidence: 99%
“…Also, different production cell lines and systems may lead to antibodies with different N-glycan profiles, not only regarding fucose residues. These may in turn affect function of antibodies since carbohydrates other than fucose, for example galactose or sialic acid may affect CDC or inflammation, respectively, among others ( 33 , 53 ). A more detailed description of the role of galactosylation and sialic acid is beyond the scope of this review.…”
Section: Strategies To Generate Therapeutic Igg1 With Low Levels Of F...mentioning
confidence: 99%
“…The core glycan structure consists of N -acetylglucosamine (GlcNAc) and mannose residues, and may be modified by the addition of fucose, GlcNAc, galactose, and sialic acid ( Figure 1B ). Indeed, much interest in IgG glycosylation has stemmed from studies that demonstrated the effects of variable glycosylation on Fc function, including afucosylated IgG gaining enhanced binding to FcγRIIIA and more potently triggering antibody-dependent cytotoxicity in vivo than fucosylated IgG ( 21 25 ). Additionally, work from our group and others has shown that terminal sialylation of the IgG Fc glycan conveys antiinflammatory activity ( 26 , 27 ), and notably, approximately 10% of glycans in IVIG are terminally sialylated ( 1 , 26 ).…”
Section: Introductionmentioning
confidence: 99%